Estudio de adsorción de cromo (III) de aguas residuales de curtiembres con la utilización de compost - Miranda Urrutia, Juan Carlos (2018)
The present research work shows the study of chromium adsorption of wastewater from tanneries with the use of compost. To develop this, it was necessary to conduct a physico-chemical characterization of three different compost brands where Agropesa was selected since it was the most adequate based on the amount of fiber (lignin and holocellulose), these compounds are considered to be responsible for the adsorbent capacity of the compost. For the isotherm determination to be adjusted to the process, Batch tests were applied on jar test equipment, using water prepared with Basic Chromium Sulphate which is the tanning agent used in the Chromium tanning process. It was necessary to work with three different concentrations of chromium in water (500, 1000, 1500 ppm) and three different amounts of fiber (10, 25, 50 grams) of the brand Agropesa, which corresponds to 17.5, 43.76 and 87.52 grams of compost respectively. From data processing, the Redlich-Peterson model, which corresponds to a combined isotherm of Langmüir and Freundlich, was the one that best fits the adsorption equilibrium. Finally, tests were carried out on two columns of fixed bed with the use of 30 cm of compost as adsorbent material and with the residual water of the tanning process to the Chromium of the Tannery Inca, which passed through the columns with a flow of 40 milliliters per minute, presenting a residual chromium concentration of 9997,097 ppm, obtaining the corresponding rupture curve. The saturation time of the bed under these conditions was approximately 10 minutes, obtaining a removal of 87.16 percent chromium.